Book Review: Waqf as a Pillar of Civilization - Rahman, Fathan Aulia (SMART Insight, 2024)
The book ‘Bir Medeniyetin İz Düşümü Vakıflar’ (Waqf as a Pillar of Civilization), written by a team of Turkish history and economics experts under the Directorate General of Waqf, presents a comprehensive study of the development of waqf from the pre-Islamic era to the glory of the Ottomans. This book emphasizes the spiritual and socio-political dimensions of waqf, by describing various definitions of scholars, the practice of waqf by the Prophet and his companions, and its evolution in classical Muslim, Seljuk, and Ottoman societies. The authors classify the types of waqf, present profiles of waqf donors from the elite to the general public, and provide real examples of waqf objects such as mosques, madrasas, hospitals, caravanserais, libraries, as well as cash waqf and avarız. The analysis also highlights the dual function of waqf as a means of worship and a social instrument for equitable welfare, while remaining closely linked to political interests. Written in a communicative style, with illustrations and rich references, this book offers an important foundation for readers and researchers who wish to understand the role of waqf in building Islamic civilization, particularly during the Seljuk and Ottoman eras.